Dynamic of Mixed HCV Infection in Plasma and PBMC of HIV/HCV Patients Under Treatment With Peg-IFN/Ribavirin. Issue 43 (October 2015) - Bagaglio, Sabrina; Uberti-Foppa, Caterina; Di Serio, Clelia; Trentini, Filippo; Andolina, Andrea; Hasson, Hamid; Messina, Emanuela; Merli, Marco; Porrino, Lucy; Lazzarin, Adriano; Morsica, Giulia
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The extent of mixed hepatitis C virus (HCV) genotype in different compartments (plasma and peripheral blood mononuclear cell, PBMC) and possible association with treatment efficacy in HIV/HCV coinfected patients remains to be unknown. The objective of this study was to elucidate the frequency of mixed genotype infection (MG), its profile in different compartments during anti-HCV treatment, and the possible influence of different genotypes on the response rate. The compartmentalization of HCV population was investigated by next-generation sequencing in 19 HIV/HCV coinfected patients under anti-HCV treatment with peginterferon/ribavirin (P–R). Ten individuals were nonresponder (NR) or relapser (RE) to P–R treatment and 9 had a sustained virological response (SVR). Eleven/nineteen (58%) patients had MG in plasma compartment. Ten or 12 patients infected by a difficult to treat genotype (DTG) 1 or 4 as dominant strain, had an MG, whereas only 1/7 individuals infected by easy to treat genotype (ETG) harbored a mixed genotype, P  = 0.006. HCV–RNA was more frequently detected in PBMC of NR (10/10) than in those of SVR (5/9), P  = 0.032. Mixed genotype infection was detected in 6/15 (40%) PBMC-positive cases and was not associated with P–R treatment response. By multivariate analysis, MG in plasma samples was the most important viral factor affecting the treatment response ( P  = 0.0237). Detection of MG in plasma of HIV/HCV coinfected patients seems to represent the major determinant of response to P–R treatment. This finding may have important clinical implication in light of the new therapeutic approach in HIV/HCV coinfected individuals suggesting that combination treatment with direct acting antivirals could be less effective in MG.